Efficacy of CT in the diagnosis of vascular dementia. - Glatt, S L; Lantos, G; Danziger, A; Katzman, R (American Journal of Neuroradiology, 1983)
The records of 27 consecutive patients who underwent computed tomography (CT) of the head after referral for the evaluation of dementia were reviewed to evaluate the utility of CT in the differentiation of multiinfarct dementia and senile dementia of the Alzheimer type. Using the criteria of focal parenchymal low-attenuation zones and asymmetric tissue loss, CT did not discriminate between patients with vascular dementia and those with degenerative brain disease.